Impacts of Endemic Maoridrilus Earthworms (Megascolecidae) in Biosolids‐Amended Soil. Issue 1 (1st January 2017) - Kim, Young‐Nam; Robinson, Brett; Horswell, Jacqui; Boyer, Stephane; Dickinson, Nicholas
Abstract : Biosolids can be a valuable fertilizer for agriculture and in ecological restoration, although there are concerns about contaminants. Earthworm activity, including vermicomposting of biosolids, may influence the efficacy of their use. We investigated how two New Zealand endemic anecic species of Maoridrilus (cf. Eisenia fetida ) responded to biosolids amendment and affected the mobility of nutrients and trace elements as well as greenhouse gas emissions in biosolids‐amended soil. Earthworms were incubated with mixtures of biosolids‐amended soil (0, 6.25, 12.5, 25, and 50% biosolids by volume) for 21 d. All species survived in the soil–biosolids mixtures but not in 100% biosolids. The native earthworms, Maoridrilus transalpinus and Maoridrilus sp.2, increased KCl‐extractable NH4 + and NO3 − by up to 29%, substantially more than E. fetida . All species significantly increased microbial biomass carbon and Ca(NO3 )2 –extractable Cu but significantly decreased dehydrogenase enzymes activity in biosolids‐amended soil. Concentrations of Ca(NO3 )2 –extractable Mg, S, Fe, Mn, Cd, Co, and Zn varied between earthworm species and with biosolids addition rates. New Zealand native earthworms exacerbated N2 O emissions from soil, whereas E. fetida did not. Eisenia fetida is clearly a preferred species for vermicomposting biosolids and is more tolerant of high concentrations of biosolids. However, New Zealand native earthworms may be more suitable for improving the fertility of soil amended with biosolids. Core Ideas: Locally sourced earthworms are a potential resource for the treatment of biosolids‐amended soil. Maoridrilus spp. increased biosolids mineralization more than Eisenia fetida . Native earthworms enhanced microbial activity but increased N2 O emission.